Theodor Mommsen and the collegia funeraticia: Theodor Mommsen i collegia funeraticia - Wojciechowski, Przemysław (Klio - Czasopismo Poświęcone Dziejom Polski i Powszechnym, 2025)
In 1843, Theodor Mommsen completed his legal studies at the University of Kiel; in the same year, his dissertation De collegiis et sodaliciis Romanorum appeared in print. This publication, which was small in terms of volume, not only opened the door to an illustrious academic career for its author, but also had an enormous impact on the course of scholarly discussion on Roman colleges. One of the basic concepts used in this discussion is the 'funeral colleges' created by Mommsen. The main purpose of this article is to show that we are dealing with an anachronism in this case. Mommsen's proposed concept of 'funeral colleges' found very fertile ground in Germany at the time ('bürgerliche Vereinsbewegung' and Bismarck's social reforms), but it is not substantiated by the source material. None of the known Roman colleges was a 'funeral college' in the sense in which the term was used by Mommsen and his scholarly heirs. The fact that, for many colleges, helping to organise the burial of a deceased member was an important sphere of their activity does not make them 'funeral colleges'. W 1843 roku Theodor Mommsen skończył studia prawnicze na uniwersytecie w Kilonii; w tym samym roku ukazała się drukiem jego rozprawa „De collegiis et sodaliciis Romanorum”. Ta niewielka pod względem objętości publikacja nie tylko otworzyła drzwi do wspaniałej kariery akademickiej jej autora, lecz wywarła także ogromny wpływ na przebieg dyskusji naukowej na temat rzymskiego korporacjonizmu. Jednym z podstawowych pojęć używanych w tej dyskusji są wykreowane przez Mommsena „kolegia pogrzebowe”. Głównym celem tego artykułu jest wykazanie, że mamy w tym przypadku do czynienia z anachronizmem. Zaproponowana przez Mommsena koncepcja „kolegiów pogrzebowych” trafiła na bardzo podatny grunt w ówczesnych Niemczech („bürgerliche Vereinsbewegung” i reformy społeczne Bismarcka), nie ma jednak uzasadnienia w materiale źródłowym. Żadne ze znanych rzymskich kolegiów nie było „kolegium pogrzebowym” w tym znaczeniu, w jakim tego terminu używał Mommsen i jego naukowi spadkobiercy. Fakt, że dla wielu kolegiów pomoc w zakresie organizacji pochówku zmarłego członka była ważną sferą ich aktywności, nie czyni z nich „kolegiów pogrzebowych”.